Undergraduate and postgraduate medical education on the prevention and control of healthcare-associated infection. More progress is needed - Humphreys, Hilary; Richards, Judith (International Journal of Infection Control, 2011)
The prevention and control of healthcare-associated infection (HCAI) is a significant patient safety and quality issue that has not been accorded sufficient emphasis in the medical school curriculum. Compliance amongst medical students and graduates with basic measures such as hand hygiene is inferior to that amongst other healthcare groups such as nurses. While there are some studies assessing the knowledge of medical students on HCAI prevention, few have assessed attitudes and practice or behaviour. Although, HCAI is being recognised in the medical curriculum there is scope for greater co-ordination in educational delivery and assessment. At postgraduate level, there has been some success in enhancing the prevention of catheter-associated bloodstream infection through a multi-modal approach that has been shown to be superior to traditional measures. Education programmes need to be developed at the postgraduate level geared to the specialty, but much more work needs to be done to highlight the importance of this area and to ensure better compliance.